Denby family papers
Chiefly correspondence and related material exchanged among Denby family members. The bulk of the letters are between Charles Denby (1830-1904), his wife Martha Fitch Denby, and their children Graham, Charles (1861-1938), Harriet, Wythe, Edwin, and Thomas Garvin. Also includes letters from Martha's mother Harriet Satterlee Fitch and father Graham Newell Fitch.
Includes courtship correspondence (1850s) between Charles Denby, a lawyer in Evansville, Ind., and Martha of Logansport, Ind., and Washington, D.C. Includes Civil War correspondence of Charles written while serving with the Forty-second Indiana Volunteers and the Eightieth Indiana Volunteers in Alabama, Kentucky, and Tennessee. Letters speak of life at home and in camp. Correspondence (1860s-1870s) documents family life, local and national events, and Charles's work as a lawyer. Includes letters from Denby's son Charles while he attended the College of New Jersey, Princeton, N.J., and from their daughter Harriet while she attended Hellmuth Ladies' College, London, Ont.
Correspondence (1885-1905) pertains to the elder Charles Denby's post as minister to China, the official, social, and domestic lives of the diplomatic community in Beijing, and the life of other Denby family members in China and the U.S. Includes material relating to son Charles's work in diplomatic service and business in China and Edwin's service in the Chinese Maritime Customs Service (Hai guan zong shui wu si shu). Documents the Spanish-American War in relation to Edwin's and son-in-law Gilbert Wilkes's service aboard the cruiser Yosemite in 1898 and father Charles's service on a commission investigating the conduct of the U.S. War Dept. during the war and on the U.S. Philippine Commission. Includes a journal Martha kept on a trip with the commission to the Philippines.
Correspondence (1890s-1911) document Wythe's work as a mining engineer in Alaska, Arizona, and Utah; Edwin's election to Congress, his early days in Washington, D.C., and a trip to Europe; and son Charles's work in the State Department.
Denby family members including Charles Denby (1830-1904), lawyer and U.S. minister to China; Charles Denby (1861-1938), diplomat to China; and Edwin Denby (1870-1929), congressman and U.S. secretary of the navy.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Denby, Charles, -- 1830-1904 -- Correspondence; Denby, Charles, -- 1861-1938 -- Correspondence; Denby, Edwin, -- 1870-1929 -- Correspondence; Denby, Graham -- Correspondence; Denby, Harriet -- Correspondence; Denby, Martha Fitch -- Correspondence; Denby, Thomas Garvin -- Correspondence; Denby, Wythe -- Correspondence; Fitch, Graham N. -- 1809-1892 -- Correspondence; Fitch, Harriet Satterlee -- Correspondence; Denby family; China. -- Hai guan zong shui wu si shu; United States. -- Army. -- Indiana Infantry Regiment, 42nd (1861-1865); United States. -- Army. -- Indiana Infantry Regiment, 80th (1862-1865); United States. -- Congress; United States. -- Department of State; United States. -- Philippine Commission (1899-1900); United States. -- War Department; College of New Jersey (Princeton, N.J.); Hellmuth Ladies' College (London, Ont.); Yosemite (Cruiser); Customs administration -- China; Diplomatic and consular service, American -- China; Diplomatic and consular service, American -- China -- Beijing; Mining engineering -- Alaska; Mining engineering -- Arizona; Mining engineering -- Utah; Practice of law -- Indiana -- Evansville; Spanish-American War, 1898.; Universities and colleges -- New Jersey -- Princeton; Universities and colleges -- Ontario -- London; Alabama -- History -- Civil War, 1861-1865.; China -- Commerce; China -- Foreign relations -- United States; Europe -- Description and travel; Evansville (Ind.) -- Social life and customs; Indiana -- History; Indiana -- History -- Civil War, 1861-1865.; Kentucky -- History -- Civil War, 1861-1865.; Logansport (Ind.) -- Social life and customs; Philippines -- Description and travel; Tennessee -- History -- Civil War, 1861-1865.; United States -- Foreign relations -- China; Washington (D.C.) -- Social life and customs